Leadership in implementation of quality family-centred services in early childhood: an exploration of administrators' perceptions, needs and realities. Issue 6 (25th April 2020) - Movahedazarhouligh, Sara; Banerjee, Rashida
ABSTRACT: The term family-centred practices refer to a particular set of beliefs, principles, values, and practices for supporting and strengthening family capacity to enhance and promote child development and learning. Family-centred services in early childhood and early childhood special education programmes (EC/ECSE) can affect a wide range of outcomes. However, despite research documenting the potential benefits of family-centred services, full implementation in practice is difficult to achieve. In the United States, EC/ECSE administrators struggle with implementing quality family-centred services within an environment of limited resources and competing priorities. This paper provides results from an exploratory qualitative study that investigated the administrators' perceptions, current practices and training needs, in family-centred services, and recommendations for administrators regarding implementation of quality family-centred service delivery in EC/ECSE settings.